James B. Mitchell papers - Mitchell, James B.
Correspondence from Mitchell to his parents concerning his experiences as a student at the University of North Carolina (1859-1861) and the University of Alabama (1862), as a Confederate soldier in Tennessee and Mississippi (1862-1863), and as a prisoner of war at Johnson Island Prison, Ohio (1864-1865). Includes detailed descriptions of several military actions and the conditions of military and prison camp life.
Confederate army soldier and student.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: University of North Carolina at Chapel Hill -- History; University of Alabama; Tennessee -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; Johnson Island Prison; Ohio -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865.; Soldiers -- Confederate States of America; Students